Pengaruh Media Sosial Dan Inovasi Produk Terhadap Perkembangan Usaha (Studi Kasus UMKM di Kecamatan Bululawang Kabupaten Malang) - Balqish, Alya Tamara; Mardani, Ronny Malavia; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to analyse the extent to which social media and product innovation play a role in driving the growth of businesses run by Micro, Small, and Medium Enterprises (MSMEs) in Bululawang Subdistrict, Malang Regency. This study adopts a quantitative approach with an explanatory research design, as it seeks to explain the relationship between variables empirically. The sampling technique used was purposive sampling, which involves the deliberate selection of respondents based on specific criteria, with a total of 113 MSMEs calculated using the Lemeshow formula because the population size was not known precisely. Data was collected through a questionnaire distributed to respondents. To process and analyse the data, multiple linear regression analysis was used. The results of the data analysis revealed that the simultaneous use of social media and the implementation of product innovation have a positive and significant impact on the development of SME businesses in the study area. Keywords: Social Media, Product Innovation, Business Developmen